Variability in categories of Arctic sea ice in Fram Strait. Issue 10 (27th October 2014) - Hansen, E.; Ekeberg, O.‐C.; Gerland, S.; Pavlova, O.; Spreen, G.; Tschudi, M.
Abstract An attempt to quantify the temporal variability in the volume composition of Arctic sea ice is presented. Categories of sea ice in the Transpolar Drift in Fram Strait are derived from monthly ice thickness distributions obtained by moored sonars (1990–2011). The inflection points on each side of the old ice modal peak are used to separate modal ice from ice which is thinner and thicker than ice in the modal range. The volume composition is then quantified through the relative amount of ice belonging to each of the three categories thin, modal, and thick ice in the monthly ice thickness distributions. The trend of thin ice was estimated to be negative at −8.8% per decade (relative to the long‐term mean), which was compensated for by increasing trends in modal and thick ice of 7.9% and 4.7% per decade, respectively. A 7–8 year cycle is apparent in the thin and thick ice records, which may explain a loss of deformed ice since 2007. We also quantify how the categories contribute to the mean ice thickness over time. Thick (predominantly deformed) ice dominates the mean ice thickness, constituting on average 66% of the total mean. Following the loss of deformed ice since 2007, the contribution of thick ice to the mean decreased from 75% to 52% at the end of the record. Thin deformed ice did not contribute to this reduction; it was pressure ridges thicker than 5 m that were lost and hence caused the decrease in mean ice thickness.